Mucopolysaccharidosis type VII presenting as neonatal cholestasis (Indian Journal of Case Reports, 2020)
Mucopolysaccharidosis type VII presenting as neonatal cholestasis is very rare. Here, we present the case of a 55-day-old baby presented with cholestatic jaundice. On examination, the baby had icterus, hepatosplenomegaly, and initial workup for common causes of cholestasis which were negative. Liver biopsy revealed neonatal hepatitis. On further follow-up, coarse facies were noted, and suspecting metabolic disorder, exome sequencing was done. A mutation in the GUSB gene was identified which is pathogenic for MPS VII. The neutrophils also showed the characteristic Alder–Reilly granules. Neonatal cholestasis with coarse facies should have MPS VII as a differential diagnosis. Genetic testing in doubtful metabolic conditions will provide an answer and also help in the prenatal diagnosis of future pregnancies.